2021
DOI: 10.1063/5.0063691
|View full text |Cite
|
Sign up to set email alerts
|

Photon-number squeezing in nano- and microlasers

Abstract: Based on theoretical predictions on the appearance of antibunching before the laser threshold at the nano- and microscale, we analyze the amount of photon-number squeezing naturally produced in the laser emission. Up to 3 dB photon number noise reduction is obtained in comparison with the coherent emission, with output power in the range of pW and with negligible effects due to pump fluctuations. The scheme requires a moderately high Q cavity and holds promise for the construction of a simple and effective pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…[34][35][36] Only recently has the concept of threshold definition been broadened to acknowledge that at the micro-and nanoscale, there are multiple definitions that pertain to separate points, contingent upon the quantity being analyzed 1,37 Advanced quantum mechanical models are now emerging in a context where quantum effects are significant due to the small scale, despite the averaging over tens of active emitters interacting with a cavity which possesses a limited number of resonant modes. [38][39][40][41] One significant factor in understanding the physics of laser threshold at the nanoscale, and the microscale as well, is the constraints related to measurement techniques. This contribution primarily focuses on this aspect.…”
Section: Physical Peculiarities Of Nanolasersmentioning
confidence: 99%
“…[34][35][36] Only recently has the concept of threshold definition been broadened to acknowledge that at the micro-and nanoscale, there are multiple definitions that pertain to separate points, contingent upon the quantity being analyzed 1,37 Advanced quantum mechanical models are now emerging in a context where quantum effects are significant due to the small scale, despite the averaging over tens of active emitters interacting with a cavity which possesses a limited number of resonant modes. [38][39][40][41] One significant factor in understanding the physics of laser threshold at the nanoscale, and the microscale as well, is the constraints related to measurement techniques. This contribution primarily focuses on this aspect.…”
Section: Physical Peculiarities Of Nanolasersmentioning
confidence: 99%
“…In other words, the physical mechanism of photon-number squeezing is that the fluctuation of photon number ∆ N is less than the average photon number ⟨ N⟩. It means that the photon statistics of photon number are sub-Poissonian [18]. Differently, for a four-beam seeded four-mode PSA, the IDS with regard to the SNL can be expressed as equation (6).…”
Section: Comparison Of Ids and Photon-number Squeezingmentioning
confidence: 99%
“…Quantum squeezing, an indispensable resource for quantum optics, has been widely utilized in quantum metrology [1][2][3][4][5][6] and quantum information protocols [7][8][9][10][11] due to the noise reduction nature of quantum squeezing. According to the difference of squeezed physical quantity, quantum squeezing can be classified as quadrature squeezing [12][13][14][15], photon-number squeezing [16][17][18], spin squeezing [19][20][21], and so on. For its applications in quantum metrology [22][23][24][25][26][27][28][29][30], such as laser interferometer gravitational-wave observatory (LIGO) [22,23] and laser beam positioning [24], the degree of quantum squeezing directly determines the extent to which measurement sensitivity beats the classical limit.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental work conducted in small lasers in the last decades has shown that the transition from incoherent to coherent emission differs from the one observed in macroscopic laser physics: a sudden jump from zero-to full-coherence. Rather, spontaneous squeezing has been, for instance, observed and explained with ad hoc modelling [41] together with forecasts for sizeable transient squeezing due to pulsed pumping [42], squeezing with cw pumping [43], sub-and superradiant emission [44], or superthermal emission due to mode competition [45][46][47][48][49]. The influence of physical parameters on the laser threshold are reviewed in [50], whereby the experimentally observed transition from LED-like emission to lasing [51], is explained with the help of RESE [52].…”
Section: New Phenomena Around Thresholdmentioning
confidence: 99%